2010
DOI: 10.1016/j.watres.2010.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Nitrifier characteristics in submerged membrane bioreactors under different sludge retention times

et al.

Abstract: NitrificationMicrobial ecology a b s t r a c t Nitrosomonas and Nitrobacter sp. were the dominant AOB and NOB, respectively for M 30d , while considerable slow-growing Nitrosospira and Nitrospira sp. existed in M infinite , which might be an important reason why M infinite had a low SAOR and SNFR.ª

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 39 publications
1
12
0
2
Order By: Relevance
“…It has been reported that longer SRT could impact the biological activities negatively including nitrification rate of MBR (Yu et al 2010). A study conducted by Yu et al (2010), observed a negative correlation between SRT and the nitrifier activities, i.e.…”
Section: Sludge Retention Timementioning
confidence: 96%
See 3 more Smart Citations
“…It has been reported that longer SRT could impact the biological activities negatively including nitrification rate of MBR (Yu et al 2010). A study conducted by Yu et al (2010), observed a negative correlation between SRT and the nitrifier activities, i.e.…”
Section: Sludge Retention Timementioning
confidence: 96%
“…In two different MBRs investigated (one was adapted with biofilm support medium), Liang et al (2010) noted that high nitrification rates correlated with the high species richness of nitrifying bacteria. Various authors have reported 96-99 and 92-98 % ammonia-nitrogen and COD removals, respectively, in MBRs investigated Yu et al 2010;Ozdemir et al 2011). Although a higher nitrogen removal is being reported in MBR by various authors in comparison with conventional activated sludge systems, MBRs seem not to have an edge in terms of specific nitrification rates.…”
Section: Nitrification Processmentioning
confidence: 98%
See 2 more Smart Citations
“…FISH법은 다양한 종류의 probe들을 사용하여 전체적인 박 테리아 군집에 대한 해석이 용이하며, 또한, 목적으로 하는 특정 박테리아 군집들에 대해 정성·정량적인 평가가 가능하 기 때문에 환경시료 내의 박테리아 군집 구조 분석과 모니터 링에 다양하게 적용되고 있다 [18][19][20]. 특히, 수처리 분야에서 하·폐수처리 공정내의 생물학적 처리공정의 박테리아 군집 분석 [15,16,[19][20] DAPI법에 의한 총 세균수 측정은 고정된 시료 2 µL를 gelatin으로 코팅된 slide glass에 놓고, DAPI (4',6-diamidino 2-phenylindole 1 µg/mL, Sigma, USA)로 5분 동안 염색하였 다.…”
Section: 서론unclassified